Integration of Total Maximum Daily Load (TMDL) and Environmental Flow Assessment (EFA) concepts as an adaptive approach to pollutant loading management in Asia: a review - Mohd Yusof, Fasihah; Jamil, Nor Rohaizah; Sapia’e, Syahida; Marcus Ata, Frankie; Abdul Malik, Nur Khaliesah (Universiti Putra Malaysia Press, 2025)
Water scarcity and pollution are escalating challenges in Asia, impacting ecological systems and human livelihoods. This paper reviews the integration of Total Maximum Daily Load (TMDL) and Environmental Flow Assessment (EFA) in water management to address the dual issues of water quality and quantity. TMDL focuses on regulating the number of pollutants entering water bodies to meet quality standards, while EFA ensures that enough water is available to support aquatic ecosystems. Their independent application, however, often leads to gaps—TMDL can overlook ecological needs, while EFA may neglect pollution control. The integration of these two frameworks offers a more holistic solution, especially in water-stressed regions like Southeast Asia, where moderate water availability is exacerbated by urbanization, industrialization, and agricultural runoff. Case studies from Malaysia, Indonesia, and China reveal the limitations of applying TMDL and EFA separately and underscore the necessity of addressing both ecological flow requirements and pollution limits. This paper identifies key pollutants such as biochemical oxygen demand (BOD), chemical oxygen demand (COD), heavy metals, and total suspended solids (TSS), particularly in urban and semi-urban areas, and highlights the importance of tailoring strategies to the specific needs of different regions. By combining TMDL and EFA, policymakers can better manage pollutant loads, secure ecological health, and address Asia’s pressing water management issues. This review emphasizes the need for adaptable, integrated water management strategies that account for seasonal fluctuations, competing water demands, and regional water availability and pollution differences.